I would if I could and I can - Hoke, James H. (New York : Berkley Books, 1980)
A self-help program, based on the techniques of hypnosis, that explains how to change habits, such as over-eating, or other types of behavior.
Keywords: Behavior modification; Hypnotism -- Therapeutic use